Chapter Ettore Lo Gatto a Padova - Mazzitelli, Gabriele (Firenze University Press, 2025)
Ettore Lo Gatto was a lecturer at Padua University for 12 years from 1929 to 1941, although he actually only taught there for six years, from 1930 to 1936, since in 1931 he stayed in Russia for a long time, and from 1936 to 1941, he moved to Prague as a lecturer in Italian literature at the Charles University and then as Director of the Italian Cultural Institute (Istituto Italiano di Cultura). It is to the University of Padua that Lo Gatto owes his becoming a full professor thus obtaining a permanent place in academia. The article retraces the key moments of Lo Gatto's activity in Padua, attempting to reconstruct his biographical and intellectual journey in those years while also keeping in mind the historical context in which he operated.